Growth Response and Yield of Stevia (Stevia rebaudiana) to Giving Old Coconut Water and Different Types of Irrigation - Fahima , Sahidatun; Frans Cesar Regar, Arthur (Journal of Soilscape and Agriculture, 2024)
The purpose of this study was to determine the response and yield of the stevia plant to different concentrations of old coconut water combined with two different types of irrigation, namely drip irrigation and sprinkler irrigation. The experimental design was a split plot with the RAK basic design pattern and two factors. The first factor is the use of different irrigation types, including drip and sprinkler irrigation. The second factor is the concentration of coconut water, which consists of 5 levels, namely A0 = 0% coconut water concentration, A1 = 25% coconut water concentration, A2 = 50% coconut water concentration, A3 = 75% coconut water concentration, and A4 = water concentration coconut 100%. Data analysis used the T-test to determine the effect of the type of irrigation and ANOVA to determine the impact of giving old coconut water with the F test at level α = 0.05. A DMRT test was done to measure the significant values of the ANOVA test. The results showed no interaction between different irrigation types and coconut water concentration for all observational variables. Different kinds of irrigation showed significant differences in some parameters. Giving old coconut water gives different results in each experiment.